Midwinter Dry Spells Amplify Post‐Fire Snowpack Decline. Issue 3 (1st February 2023) - Hatchett, Benjamin J.; Koshkin, Arielle L.; Guirguis, Kristen; Rittger, Karl; Nolin, Anne W.; Heggli, Anne; Rhoades, Alan M.; East, Amy E.; Siirila‐Woodburn, Erica R.; Brandt, W. Tyler; Gershunov, Alexander; Haleakala, Kayden
Abstract: Increasing wildfire and declining snowpacks in mountain regions threaten water availability. We combine satellite‐based fire detections with snow seasonality classifications to examine fire activity in California's seasonal and ephemeral snow zones. We find a nearly tenfold increase in fire activity during 2020–2021 versus 2001–2019. Accumulation season broadband snow albedo declined 25%–71% at two burned sites (2021 and 2022) according to in‐situ data relative to un‐burned conditions, with greater declines associated with increased burn severity. By enhancing snowpack susceptibility to melt, both decreased snow albedo and canopy drove midwinter melt during a multi‐week dry spell in 2022. Despite similar meteorological conditions in December–February 2013 and 2022–linked to persistent high pressure weather regimes–minimal melt occurred in 2013. Post‐fire snowpack differences are confirmed with satellite measurements. With growing geographical overlap between wildfire and snow, our findings suggest California's snowpack is increasingly vulnerable to the compounding effects of dry spells and wildfire. Plain Language Summary: Satellite fire detections indicate substantial increases in wildfire activity in California's snow‐covered landscapes during 2020 and 2021, suggesting wildfire is increasingly altering mountain hydrology. During 2022, a multi‐week mid‐winter drought, or dry spell, occurred. A meteorologically‐similar dry spell occurred in 2013, and the 2022 event provides a test case to examine how post‐fire changes (canopy loss and deposition of burned dark material on snowpack) alter snowmelt patterns. Using field observations, weather station data, and satellite remote sensing of snow, we find large reductions in snow albedo and canopy cover drove rapid melt during the 2022 dry spell in burned areas whereas during 2013, minimal melt occurred. The societal connection between mountains and humans will be strained as mountains face increasing climate‐related stressors. Midwinter drought, snow loss, and increasing wildfire are expectations of a warming world. Addressing these challenges requires innovative water and forest management paradigms. Our findings motivate additional research into assessing and planning for post‐fire hydrologic changes in snow‐dominated landscapes as both wildfire and dry spells will increase in frequency with climate warming. Key Points: A 9.8x increase in satellite fire detections in California's snow zones in 2020–2021 versus 2001–2019 implies growing overlap in fire and snow Post‐fire accumulation season broadband snow albedo declined 25%–71%, driving fewer snow‐covered days and lower snow‐cover fraction Compared with the meteorologically similar 2013 dry spell, albedo and canopy declines led to rapid midwinter melt in 2022